Modeling for estimating and optimizing the energy potential of animal manure and sewage in small and medium-sized farms - Oliveira, Augusto Cesar Laviola de; Renato, Natalia dos Santos; Martins, Marcio Arêdes; Mendonça, Isabela Miranda de; Moraes, Camile Arêdes; Resende, Michael de Oliveira (Journal of cleaner production, 2021)
The use and production of energy have a significant impact on the environment, including emissions of greenhouse gases into the atmosphere. Most of the energy consumed in the world comes mainly from fossil fuel sources. In this way, international public policy agendas have been encouraging the replacement of this energy source by renewable energy sources. The energy reuse of waste can contribute to the greater energy security through diversification of the energy matrix. Thus, the objective of this study was to develop a mathematical model capable of estimating and optimizing the allocation of energy potential, from animals manure and sewage. To achieve this objective, a deterministic constructive algorithm coupled with nonlinear model parameters was implemented. Data used for waste and sewage production were collected in farms of municipality in the state of Minas Gerais, Brazil. As a result of the calculations, a total energy potential of 1913 GWh y−1. On average, the properties taken into account in the study resulted in an estimated energy potential of 17,236.20 ± 55,137.63 kWh y−2; and those that did not have minimum potential, which economically enables the implantation of a local biogas plant, the potentials were allocated to the plants that serve a community. The average potential per plant varied between 36,792 and 54,663 kWh y−1 due to the 16 combinations between mathematical models and cases of financial analysis. A number between 35 and 52 corresponds to the number of plants that were allocated in the study municipalities and the average number of farms per plant ranged from 2.13 to 3.17. A model was adjusted to predict 92.4% of the variation in generation potential as a function of electricity consumption and farm production profit. Finally, it was validated that the perpestive of investment in renewable energy by a rural producer is dependent on the knowledge he has on the subject and on what he consumes on his property. The mathematical modeling to represent the optimization problem was implemented in a generic way, so it is capable of being applied to other energy systems, being able to point out good solutions considering environmental and financial issues. The results showed a robust, efficient, and adaptable model. [Display omitted] •Cleaner Production and Technical processes.•Sustainable Development and Sustainability.•Environmental and Sustainability Assessment.•Evaluation of energy potential from organic waste.•Mathematical model and optimization technique for the allocation of energy resources.